Jacobi matrices associated with the inverse eigenvalue problem in the theory of singular perturbations of self-adjoint operators - Koshmanenko, V. D.; Tuhai, H. V. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We establish the relationship between the inverse eigenvalue problem and Jacobi matrices within the framework of the theory of singular perturbations of unbounded self-adjoint operators.